Diversity and structure of microbial biofilms on microplastics in riverine waters of the Pearl River Delta, China - Yang, G.; Gong, M.; Mai, L.; Zhuang, L.; Zeng, E. Y.
Riverine runoff is a significant transport pathway for microplastics (MPs)discharged from land-based sources to marine environments where MPs accumulate. Knowledge of riverine MP-associated biofilms will improve the understanding of the fate and potential effects of MPs in marine environments. This study aimed to characterize the microbial biofilms colonizing MPs in the riverine water of the Pearl River Delta, China, and identify the seasonal, geographical and environmental influences on MP-associated communities. We sampled MPs and the surrounding surface water from eight outlets in three seasons and analyzed their microbial communities by Illumina sequencing of the 16S rRNA gene libraries. Across all sampling seasons and locations, abundant MP-colonizing taxa belonged to the phylum Proteobacteria, which suggested initial biofilm development on those MPs. The structure and composition of MP-attached microbial communities varied with respect to season and location, and the microbial diversity of the MP-associated biofilm communities decreased in June compared with that in the April and November sampling events. Opportunistic pathogens of the genus Acinetobacter were significantly enriched on the MP surfaces for all sampling events. Among the 15 environmental variables examined, the main drivers of MP-associated biofilm community composition included IC, alkalinity, TOC, TDS, Cl?, NO3?, NO2? and pH. This study provides an insight into the environmental factors that shape microbial biofilm colonization on MPs in estuary environments and a further understanding of the structure, diversity and ecological roles of MP-associated communities.
Keywords: MICROPLASTICS; RIVERINE WATER; BIOFILM COMMUNITY; ENVIRONMENTAL VARIABLES; OPPORTUNISTIC PATHOGENS